High-entropy spinel oxides for water oxidation: surface entropy evolution and activity promotion - Wang, Jiarui (2024)
In recent years, the concept of entropy stabilization has led to increased research in “high-entropy materials”. These compounds incorporate multiple metals into a single crystalline phase, resulting in interactions between them that offer novel and unexpected properties. Here, we report on the surface evolution and entropy changes of the high-entropy spinel oxide (HEO) Zn(CrMnFeCoNi)2O4 upon its use as an electrocatalyst for the oxygen evolution reaction (OER). It was found that electrochemical cycling of this material results in surface reconstruction accompanied by induced leaching of surface Zn from the tetrahedral sites. The formation of a completely new metal (oxy)hydroxide Zn2Cr1.5Mn2Fe1Co2Ni1.5OxHy is observed at the surface, leading to an increase in surface entropy over the pristine spinel HEOs. The newly formed surface exhibits improved OER catalytic performance through the adsorbate evolution mechanism (AEM). Removing any one of the cations from this HEO results in a significant decrease in the OER performance. This shows that the electrochemical behavior of the high-entropy oxides depends on each of the metal ions present on the catalyst’s surface, thus providing the opportunity to tailor its electrochemical properties by simply changing the elemental composition.